A Study Knowledge About Pregnancy Breast Careat the BPS Etty J, Amd. Keb In Sukorejo Village Gurah Sub Distric Kediri Regency - Wati, Susi Erna (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2015)
ABSTRACT Breastcareduringpregnancyisan important partto notein preparation fora feeding. Breastcareis notonlydoneafterthe birth.Treatment doneaimingfor blood circulationandpreventcloggedmilk ductsto facilitateexpendituresmilk. This study aimstoidentify apicture ofthirdtrimesterpregnant womenknowledgeabout thedesign oftreatmentstudies usingdescriptivemethods. The population inthis study were allpregnant womeninthird trimesterofcontrolBPSEtty J.Keb In Sukorejo Village Gurah Sub Distric Kediri Regency on March to April 2014.With asampleof 18respondents, thesamplingtechniqueused istotalsampling. Data collectionusingquestionnaires. Tabulationof dataprocesseddata. Based on this researchcan result in16 respondents(88%) knowledgeableenoughaboutbreast careduringpregnancy, in the canfirstresponders(6%) bothknowledgeableaboutbreast careduringpregnancyandin the canfirstresponders(6%) are lessknowledgeableaboutbreast careduringpregnancy. Thus it canbe concludedmost of therespondentshavesufficientknowledgeaboutbreast care. Breastcareis animportant thing to bedonebya motherbecausethe more we arediligent inbreastcareduringpregnancy, thecolostrumwill expedite theexpenditureso thatthemothernotto worryand no need toprovidethe intake ofother foodsforinfants.   Keywords: Knowledge, Mother Pregnancy, BreastCare